Gauging the Use of and Satisfaction with Home Grown Electronic Journals: A Malaysian Case Study - Rani, H.A.; Zainab, A.N. (Masters of Library of Inf. Sci. Program Uni. of Malaya, 2006)
This study examines the users of electronic journals published in a hosting system called EJUM (Electronic Journal of the University of Malaya) and their perceived satisfaction with the electronic journals as well as their preferred features in electronic journals and problems they face when using the electronic journals. The Malaysian Journal of Computer Science (MJCS), Malaysian Journal of Library & Information Science (MJLIS) and Journal of Problem Based Learning (JPBL) are being hosted by EJUM. These three electronic journals constitute 3 out of an estimated 17 electronic journals published in Malaysia. Users seem to use the electronic journals to mainly support research and teaching needs. About 50% of respondents rated the journals as “good”, 20.6% rated “fair”. Respondents seem to find out about the journals mainly serendipitously as they were browsing the Internet or “found out from a conference paper” or “saw information about it in an article”. Keywords (28.9%) and title (24.3%) searches were chosen by a third of respondents respectively. The majority of respondents (70%) indicated preferring retrieving articles in PDF or HTML. About 41.8% of respondents access the electronic journals while making searches on Google or Yahoo. The next most selected option was “from specific journal hosting system” (21.8%), followed by “from my library web portal” and “from citation links found in another resource”. Most respondents scan the abstracts first to check relevance and then download the articles. Most respondents believed that electronic journals will co-exist with print journals (46.2%). The rest believed that electronic journals will replace the print journals (25.5%) or will supplement (25.5%). The list of functions and features preferred by electronic journal is provided.